Intramolecular Cyclopropanation of Bromodiazoacetates - Bolsønes, Marianne; Bonge-Hansen, Hanne Therese; Bonge-Hansen, Tore (Synlett, 2014)
A series of allylic diazoacetates were prepared from the corresponding allylic alcohols and bromoacetyl bromide. When the allylic diazoacetates were treated with 1,8-diazabicyclo[5.4.0]undec-7-ene and N-bromosuccinimide, a rapid full conversion to the corresponding allylic bromodiazoacetates occurred. Exposure of the allylic bromodiazoacetates to rhodium(II) catalysts induced an intramolecular cyclopropanation and gave cyclopropyl bromolactones in yields that were low to good, depending on the substitution pattern.
Keywords: cyclization; diazo compounds; fused ring system; rhodium; catalysis; carbenoids